Development of SaraHome: A novel, well-accepted, technology-based assessment tool for patients with ataxia. (May 2020) - Summa, Susanna; Schirinzi, Tommaso; Bernava, Giuseppe Massimo; Romano, Alberto; Favetta, Martina; Valente, Enza Maria; Bertini, Enrico; Castelli, Enrico; Petrarca, Maurizio; Pioggia, Giovanni; Vasco, Gessica
Highlights: SaraHome tracks body and hands movements by the output signals of Kinect and Leap Motion. The software is based on services provided by a Restful interface which provides a series of plugins. 6 of 8 SARA's tasks are recorded: gait, stance, sitting, speech, finger chase and fast alternating hands movement. High interest and participation from patients. Substantial satisfaction and a perception of ease of use from the parents involved in the assessment. Abstract: Background and objective: Early onset ataxias (EOAs) are a heterogeneous group of neurological conditions, responsible for severe motor disability in paediatric age, which still lack reliable outcome measures. Available scales to assess ataxia, such as the Scale for Assessment and Rating of Ataxia (SARA), are based on subjective assessment of specific motor and language tasks by an examiner, and therefore is age dependent and lacks accuracy in detecting small variations in disease severity. In last years, novel technologies, including computer interfaces and videogames, have emerged for clinical applications and the advent of Internet of Medical Things and of Information Communication Technology have allowed the remote control of such technologies. This pilot study describes a newly developed tool (SaraHome) for the assessment at home of EOA evaluating its feasibility and acceptability on a small sample of children. Methods: Ten EOA children and ten caregivers have been enrolled for a preliminary outpatient evaluation. The Microsoft Kinect 2.0 and Leap Motion Controller (LMC) connected to a personal computer with an ad hoc software have been set-up, for the acquisition of standardized motor tasks performed by the patients with the caregivers' assistance. Acceptance and practicability have been tested by QUEST 2.0 and IMI questionnaires in caregivers and patients respectively. Results: The SaraHome software was developed, based on a collection of services provided by a complex architecture that consists of a Restful interface, which enables to access a series of plugins for the execution of different tasks. A graphical user interface allows the acquisition of the patient movements while performing a motor task. A protocol of standard tasks inspired by SARA was established, and a system of video-assisted instruction provided. The set-up for the optimal acquisition of such protocol by Kinect and LMC has been defined. Both patients and caregivers accomplished the SaraHome assessment with good feedback at the technology acceptance questionnaires. Conclusions: SaraHome represents a newly developed tool for the assessment of ataxia in patients, resulting from the integration of low-cost and easy-accessible technologies. This pilot application highlighted the feasibility and the acceptability of the system, suggesting the potential use in clinical practice.